Riparian trees and aridland streams of the southwestern United States: An assessment of the past, present, and future. (December 2016) - Smith, D. Max; Finch, Deborah M.
Abstract: Riparian ecosystems are vital components of aridlands within the southwestern United States. Historically, surface flows influenced population dynamics of native riparian trees. Many southwestern streams has been altered by regulation, however, and will be further affected by greenhouse warming. Our analysis of stream gage data revealed that decreases in volume of annual discharge and mean peak discharge and a shift to earlier peak discharge will occur in the Southern Rockies region of Colorado, New Mexico, and Utah. These changes will likely decrease rates of reproduction and survival of cottonwood ( Populus fremontii and Populus deltoides ssp. wislizenii ), Goodding's willow ( Salix gooddingii ), and boxelder ( Acer negundo ), which rely on surface flows to stimulate germination and recharge groundwater aquifers. Streams in the Central Highlands of Arizona and New Mexico will likely see reductions in annual discharge volume, which could limit reproduction and survival of the above taxa and Arizona sycamore ( Platanus wrightii ). These effects may be exacerbated by demands of expanding urban areas and agricultural operations, but could also be ameliorated by increasing water use efficiency and environmental mitigation. These factors must be considered, along with climate projections, when planning for conservation of riparian trees and the animal communities they support. Highlights: Large trees are a key component of riparian ecosystems in the southwestern United States. Streamflow dynamics, which influence riparian tree populations, vary among southwestern streams. Projected streamflow characteristics vary among streams as well. Future dynamics of riparian forests will be influenced by geophysical setting, woody plant composition, and human activity.